2016
DOI: 10.1038/srep38796
|View full text |Cite
|
Sign up to set email alerts
|

Extreme ultraviolet resonant inelastic X-ray scattering (RIXS) at a seeded free-electron laser

Abstract: In the past few years, we have been witnessing an increased interest for studying materials properties under non-equilibrium conditions. Several well established spectroscopies for experiments in the energy domain have been successfully adapted to the time domain with sub-picosecond time resolution. Here we show the realization of high resolution resonant inelastic X-ray scattering (RIXS) with a stable ultrashort X-ray source such as an externally seeded free electron laser (FEL). We have designed and construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…of SPIE Vol. 11493 114930A-6 RIXS instrumentation exists (see for example 11 ), yet non-direct beam scattering is rarely taken into account. We believe the union concept can provide instrument developers and beamlines scientists a unique handle to understand the sometimes complicated interplay between scattering elements in a beamline.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…of SPIE Vol. 11493 114930A-6 RIXS instrumentation exists (see for example 11 ), yet non-direct beam scattering is rarely taken into account. We believe the union concept can provide instrument developers and beamlines scientists a unique handle to understand the sometimes complicated interplay between scattering elements in a beamline.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…3 . Many RIXS spectrometers/beamlines all over the world optimized for shorter wavelengths (MERIXS at the Advanced Light Source ( Chuang et al , 2012 ), ADRESS at the Swiss Light Source ( Strocov et al , 2010 ), the commercial Scienta XES 355 RIXS spectrometer at FERMI FEL ( Dell'Angela et al , 2016 ), and AERHA at Soleil ( Chiuzbăian et al 2014 , etc. ), are based on a scheme with a variable line spacing grating, sometimes in combination with an additional focusing mirror.…”
Section: The Experimental Setupmentioning
confidence: 99%
“…Utilizing RIXS within a pump-probe scheme—either optical pump x-ray probe or all x-ray pump-probe—makes it a very powerful technique to study the dynamics of involved states and their interactions. Such experiments have already been performed in the past at FLASH ( Beye et al , 2010 ), at the Linac Coherent Light Source (LCLS) ( Wernet et al , 2015 , Dell'Angela et al , 2013 and Dean et al , 2016 ) as well as at the Center for Free-Electron Laser Radiation for Multidisciplinary Investigations (FERMI) ( Dell'Angela et al , 2016 ) and recently again at the LCLS ( Parchenko et al , 2020 ) on different systems ranging from strongly correlated materials to catalysts. Beye et al clearly demonstrated the first-order nature of the liquid–liquid phase transition in silicon via time-resolved soft x-ray emission spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is almost never the case in pump-probe experiments on solid-state samples, utilizing one of the XUV probing techniques [e.g. X-ray magnetic circular dichroism (XMCD) (Pfau et al, 2012;Willems et al, 2015) and resonant inelastic X-ray scattering (Dell'Angela et al, 2016)]. There, the spatio-temporal overlap between THz and XUV and in particular diffraction-limited focusing of the THz beam have to be achieved with the aid of versatile in-vacuum diagnostics.…”
Section: Introductionmentioning
confidence: 99%